GE_GERICHTE P/1767/2024 vom 20. Juni 2025 - GE Cour de justice (2025)
PLAINTE PÉNALE;CLASSEMENT DE LA PROCÉDURE;DÉTENTION ILLICITE;EXPULSION(DROIT PÉNAL) | CP.30; CP.66.ala bis; CP.186; CPP.329; CPP.431.al2